Validity of the multistage 20-M shuttle-run test for japanese children, adolescents, and adults - Matsuzaka, A.; Takahashi, Y.; Yamazoe, M.; Kumakura, N.; Ikeda, A.; Wilk, B.; Bar-Or, O. (Pediatric Exercise Science, 2004)
The purpose of this study was to examine the validity of a 20-m shuttle-run test as an aerobic fitness test for Japanese children, adolescents, and young adults. Participants were 62 boys and 70 girls aged 8-17 years and 56 men and 99 women aged 18-23 years. Stepwise regression analysis was used to elucidate the relationship between shuttle-run performance, age, gender, and anthropometric parameters (as independent variables) and peak oxygen uptake (VO2peak), determined directly on a treadmill, as a dependent variable. We observed high multiple correlations for adults (R2 = .88) and for children and adolescents (R2 = .80). Therefore, it is suggested that our multiple regression equations are more appropriate for predicting VO2peak in Japanese children, adolescents, and adults.